Military Professionalism in Democratic Systems: A Comparative Study - Ramadhan Arifal; Yusa Djuyandi (Journal La Sociale, 2026)
This study analyzes military professionalism in democratic political systems through a comparative examination of Indonesia and Japan. It focuses on how military institutions in both countries implement key principles of professionalism, including political neutrality, civilian control, and the restriction of military involvement in politics. The research employs a qualitative comparative approach using a most-different systems design to capture variations across distinct historical and institutional settings. Data are collected through a literature review and in-depth interviews with a defense official and an academic expert, and are analyzed using thematic coding based on the selected indicators. The findings reveal that Japan demonstrates a more consolidated form of military professionalism, characterized by a clear institutional separation between military and political spheres, consistent civilian supremacy, and strong internalization of neutrality norms. In contrast, Indonesia has established formal democratic mechanisms to ensure civilian control but continues to face practical challenges due to the extensive involvement of the military in domestic affairs. This condition reflects a hybrid model of military professionalism, where formal subordination to civilian authority coexists with flexible roles beyond core defense functions. The study concludes that military professionalism is shaped not only by institutional design but also by historical legacies, state capacity, and the degree of normative internalization, which collectively influence the quality of civil-military relations in democratic systems.